Integrating Network Pharmacology and Experimental Validation to Decipher the Mechanism of Action of Huanglian Jiedu Decoction in Treating Atherosclerosis - Liang J; Huang Y; Mai Z; Zhan Q; Lin H; Xie Y; Wang H; Liu Y; Luo C (Dove Medical Press, 2021)
Jiahua Liang,1,* Yingjie Huang,1,* Zhexing Mai,1,* Qunzhang Zhan,1 Hengchen Lin,1 Yuxin Xie,1 Haihao Wang,1 Yan Liu,1 Chuanjin Luo2 1The First Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 2The Department of Cardiovascular Disease, Guangzhou University of Traditional Chinese Medicine First Affiliated Hospital, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanjin LuoThe Department of Cardiovascular Disease, Guangzhou University of Traditional Chinese Medicine First Affiliated Hospital, Jichang Road 16#, District Baiyun, Guangzhou, 510405, Guangdong, People’s Republic of ChinaEmail Gztcm1964@163.comBackground: This study used network pharmacology, molecular docking and experimental validation to assess the effects of Huanglian Jiedu Decoction (HLJDD) on atherosclerosis (AS).Methods: The components and targets of HLJDD were analyzed using the Traditional Chinese Medicine Systems Pharmacology database, and information on the genes associated with AS was retrieved from the GeneCards and OMIM platforms. Protein–protein interactions were analyzed using the STRING platform. A component–target–disease network was constructed using Cytoscape. GO and KEGG analyses were performed to identify molecular biological processes and signaling pathways, and the predictions were verified experimentally. Molecular docking was conducted with ChemOffice software, PyMOL software and Vina to verify the correlation of targets and compounds.Results: HLJDD contained 31 active compounds, with quercetin, kaempferol, moupinamide and 5-hydroxy-7-methoxy-2-(3,4,5-trimethoxyphenyl)chromone as the core compounds. The most important biotargets of HLJDD in AS were ICAM-1, CD31 and RAM-11. The molecular docking results showed that the molecular docking interaction energy between the 3 key targets and the 4 high-degree components were much less than − 5 kJ∙mol− 1. The experimental validation results showed that HLJDD might treat AS mainly by reducing TC, TG and LDL-C and increasing HDL-C, upregulating CD31 expression, reducing ICAM-1 and RAM-11 expression, and downregulating inflammatory factors, including CRP, IL-6 and TNF-α. These results support the network pharmacology data and demonstrate that HLJDD affects the expression of core genes and alters the leukocyte transendothelial migration signaling pathway.Conclusion: Based on network pharmacology and experimental validation, our study indicated that HLJDD exerted anti-AS effect through upregulating CD31 expression and reducing the expression of ICAM-1 and RAM-11. HLJDD may be a potential therapeutic drug to the prevention of AS.Keywords: Huanglian Jiedu Decoction, atherosclerosis, network pharmacology, molecular docking, experimental validation